Positive-Self and Negative-Other Representation in the Online News Behind Indonesia’s Anti-Chinese Riots and Indonesia Turns Its Chinese into Scapegoats - Kiantoro Andiek Setiawan; Nurul Chojimah; Ismatul Khasanah (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2018)
Anti-Chinese riots (1998) was reported in Behind Indonesia’s Anti-Chinese Riot and Indonesia Turns Its Chinese into Scapegoats. This study aims to reveal the ways how lexical choices in articles constructed positive-self [henceforth (+)] and negative-other [henceforth (-)] representation. Van Dijk’s Critical Dis-course Analysis was used specifically on the lexical choice to analyze discourse. The socialism and liberal-ism theories were examined to analyze cognition and the history of Chinese Indonesians in Indonesia was explored to analyze society. Finding shows the article uses biased lexical choices. The articles represent Chinese Indonesian as a victim; Indonesian Government, Police, Military, Press, Moslem as a provocateur; and Native Indonesians as a prosecutor. Also, the articles present social and liberal ideology. Hence, the readers must be aware of the representation since it can shape their belief.